An ice‐core proxy for northerly air mass incursions into West Antarctica - Daniel A. Dixon; Paul A. Mayewski; Ian D. Goodwin; Gareth J. Marshall; Rhaelene Freeman; Kirk A. Maasch; Sharon B. Sneed (International Journal of Climatology, 2012)
A 200‐year proxy for northerly air mass incursions (NAMI) into central and western West Antarctica is developed from the examination of 19 shallow (21–150 m deep) Antarctic ice‐core non‐sea‐salt (nss) Ca 2+ concentration records. The NAMI proxy reveals a significant rise in recent decades. This rise is unprecedented for at least the past 200 years and is coincident with anthropogenically driven changes in other large‐scale Southern Hemisphere (SH) environmental phenomena such as greenhouse gas (GHG) induced warming, ozone depletion, and the associated intensification of the SH westerlies. The Hysplit trajectory model is used to examine air mass transport pathways into West Antarctica. Empirical orthogonal function analysis, in combination with trajectory results, suggests that atmospheric circulation is the dominant factor affecting nssCa 2+ concentrations throughout central and western West Antarctica. Ozone recovery will likely weaken the spring‐summer SH westerlies in the future. Consequently, Antarctica could lose one of its best defences against SH GHG warming. Copyright © 2011 Royal Meteorological Society